TTC5 mediates autoregulation of tubulin via mRNA degradation - Lin, Zhewang; Peters, Niklas (Science, 2020)
Mechanism of tubulin autoregulation - Cells tightly control the abundance of key housekeeping factors, such as ribosomes and chaperones, to maintain them at optimal levels needed for homeostasis. Most abundance control mechanisms involve feedback regulation of mRNA transcription, but others, such as tubulins, are regulated by highly specific mRNA degradation. Lin et al. found that tetratricopeptide protein 5 (TTC5) binds to nascent alpha and beta tubulins on translating ribosomes to trigger degradation of their associated mRNAs when excess tubulin is present (see the Perspective by Shoshani and Cleveland). In the absence of TTC5-mediated tubulin autoregulation, cells display error-prone chromosome segregation, a process critically dependent on tubulin concentration. - Science, this issue p. 100; see also p. 29 - Tubulins play crucial roles in cell division, intracellular traffic, and cell shape. Tubulin concentration is autoregulated by feedback control of messenger RNA (mRNA) degradation via an unknown mechanism. We identified tetratricopeptide protein 5 (TTC5) as a tubulin-specific ribosome-associating factor that triggers cotranslational degradation of tubulin mRNAs in response to excess soluble tubulin. Structural analysis revealed that TTC5 binds near the ribosome exit tunnel and engages the amino terminus of nascent tubulins. TTC5 mutants incapable of ribosome or nascent tubulin interaction abolished tubulin autoregulation and showed chromosome segregation defects during mitosis. Our findings show how a subset of mRNAs can be targeted for coordinated degradation by a specificity factor that recognizes the nascent polypeptides they encode. - Nascent tubulin polypeptides are recognized on the ribosome by TTC5 (tetratricopeptide protein 5) to trigger tubulin mRNA decay. - Nascent tubulin polypeptides are recognized on the ribosome by TTC5 (tetratricopeptide protein 5) to trigger tubulin mRNA decay.
Gesehen am 18.02.2020